Increased posterior cingulate cortex blood flow in cancer-related fatigue - Raizen, David; Bhavsar, Rupal; Keenan, Brendan T.; Liu, Patrick Z.; Kegelman, Timothy P.; Chao, Hann-Hsiang; Vapiwala, Neha; Rao, Hengyi (Frontiers in Neurology, 2023)
Fatigue is a common and often debilitating symptom associated with cancer treatments, yet, brain mechanisms underlying cancer-related fatigue (CRF) and its progression following therapy are poorly understood. Previous studies have suggested a role of the default mode network (DMN) in fatigue. In this study we used arterial spin labeling (ASL) perfusion functional magnetic resonance imaging (fMRI) and compared resting cerebral blood flow (CBF) differences in the posterior cingulate cortex (PCC), a core hub of the DMN, between 16 patients treated with radiation therapy (RAT) for prostate (9 males) or breast (7 females) cancer and 18 healthy controls (HC). Resting CBF in patients was also measured immediately after the performance of a fatiguing 20-minute psychomotor vigilance task (PVT). Twelve of 16 cancer patients were further followed 3-6 months after completion of the RAT (post-RAT). Patients reported elevated fatigue on RAT in comparison to post-RAT, but no change in sleepiness, suggesting that the underlying neural mechanisms of CRF progression are distinct from those regulating sleep drive progression. Compared to HC, patients showed significantly increased resting CBF in the PCC and the elevated PCC CBF persisted after the PVT and during the follow up visit. Post-PVT, but not pre-PVT, resting CBF changes in the PCC correlated with fatigue changes after therapy, suggesting that PCC CBF following a fatiguing cognitive task may be a biomarker for CRF recovery.